The mutant p53-ID4 complex controls VEGFA isoforms by recruiting lncRNA MALAT1 - Pruszko, Magdalena; Milano, Elisa; Forcato, Mattia; Donzelli, S.; Ganci, Federica; Di Agostino, Silvia; De Panfilis, Simone; Fazi, Francesco; Bates, David O.; Bicciato, Silvio; Zylicz, Maciej; Żylicz, Alicja; et al. (Nature Publishing Group, 2017)
The abundant, nuclear-retained, metastasis-associated lung adenocarcinoma transcript 1 (MALAT1) has been associated with a poorly differentiated and aggressive phenotype of mammary carcinomas. This long non-coding RNA (lncRNA) localizes to nuclear speckles, where it interacts with a subset of splicing factors and modulates their activity. In this study, we demonstrate that oncogenic splicing factor SRSF1 bridges MALAT1 to mutant p53 and ID4 proteins in breast cancer cells. Mutant p53 and ID4 delocalize MALAT1 from nuclear speckles and favor its association with chromatin. This enables aberrant recruitment of MALAT1 on VEGFA pre-mRNA and modulation of VEGFA isoforms expression. Interestingly, VEGFA-dependent expression signatures associate with ID4 expression specifically in basal-like breast cancers carrying TP53 mutations. Our results highlight the key role for MALAT1 in control of VEGFA isoforms expression in breast cancer cells expressing gain-of-function mutant p53 and ID4 proteins.